Analisis Keluarga yang Mempunyai Anak Pengguna Napza Menjalani Kehidupan di Masyarakat - Batubara, Salama Thomasita; Yeni, Roza Indra; Bayuningsih, Ratih; Handyani, Eka; Suharti, Neli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aim of the research is to find out the experiences of families who have drug-using children living in society. This research uses a cross-sectional design. This research method uses a cross-sectional design. The research results show that the p-value = 0.000 is smaller than the α = 0.05, which means that there is an influence on the experience of families who have drug-using children living in society. Conclusion through the Family, it is hoped that the community health center will always be responsive and proactive to all problems experienced by families who have children who use drugs. Keywords: Drugs, Society, Family Experience